Understanding the implementation of an at-home language test: A case of an online version of TOEFL-PBT - Rahmatillah, Refanja; Fajrita, Rizki; Rahma, Endah Anisa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
An at-home test is a unique mode of language test delivery as a result of mass-gathering prohibition during the COVID-19 pandemic. Despite the uniqueness, little is known about how to effectively implement an at-home test. This study aims to provide a deeper understanding of the test by exploring the execution of the online version of TOEFL-PBT in the Language Center of Syiah Kuala University. Four test administrators were interviewed to share their experiences and opinions related to considerations for implementing an at-home proficiency test, which includes technological resources, security, and validity concerns. The data were then analyzed descriptively. The results of this study revealed that the Language Center used Safe Exam Browser to deliver the test and Zoom to supervise the test-takers in real time. The proctors could stop the test and privately investigate the test takers using the Zoom Breakout feature. The validity of the test was claimed not to be a concern since the test provider used the same form of questions as the offline version. In addition, the Language Center expressed exhaustion in carrying out the online test, thus suggesting the development of a less complicated procedure of an at-home test.